Identification of a Cholinergic Modulatory and Rhythmogenic Mechanism within the Lamprey Respiratory Network - Mutolo, Donatella (J Neurosci, 2011)
Acetylcholine (ACh) is well known to be involved in the control of breathing. However, no information is available on the role of ACh receptors (AChRs) within the lamprey respiratory network. The present study was performed on in vitro brainstem preparations of adult lampreys to investigate whether ACh affects respiratory activity possibly through an action on the paratrigeminal respiratory group (pTRG) that has been identified as an essential component of the respiratory network. Respiratory activity was monitored as vagal motor output. Bath application of 100 μm physostigmine or 1 μm nicotine increased respiratory frequency, while bath application of 100 μm d-tubocurarine or 0.25 μm α-bungarotoxin reduced respiratory frequency and increased the duration of vagal bursts. Since these effects were mimicked by microinjections of the same drugs into the pTRG, ACh proved to influence respiratory activity by acting on α7 nicotinic AChRs located within the pTRG. During apnea caused by partial blockade of ionotropic glutamate receptors at the level of the pTRG, bath application of bicuculline and strychnine restored the respiratory rhythm, although at reduced frequency. Similar results were obtained by the concurrent removal of both fast synaptic excitatory and inhibitory transmission. Blockade of pTRG α7 nicotinic AChRs suppressed this respiratory activity, thus indicating that pTRG neurons expressing these receptors contribute to respiratory rhythm generation. Together, these findings identify a novel cholinergic modulatory and possibly subsidiary rhythmogenic mechanism within the respiratory network of the adult lamprey and encourage further studies on the respiratory role of cholinergic receptors in different animal species.